1993
DOI: 10.1071/ch9930095
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Synthesis of Some Minor Xanthones From the Lichen Rinodina thiomela

Abstract: The total synthesis of the xanthones 5,7-dichloro-8-hydroxy-2-methoxy-1,3-dimethyl-9H-xanthen-9-one(10),5,7-dichloro-2,8-dihydroxy-1,3-dimethyl-9H-xanthen-9-one(11),2-dechloro-8-O-methylthiomelin (6), 2-dechlorothiomelin (8), 4-dechloro-8-O-methylthiomelin (7), 4-dechlorothiomelin (5) and northiomelin (9) has been achieved. The compounds (5)-(7) and (10) were shown to be identical to the corresponding xanthones isolated from the lichen Rinodina thiomela, while chromatographic comparisons confirmed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
0
12
0
2
Order By: Relevance
“…In contrast to the globosuxanthones and diversolonic esters (which can be considered to belong to the "type-B" tetrahydroxanthone family), most other hydrogenated xanthones have the ester group at the angular C4a position, as shown in the selected structures 17 and 18 ("type-A" tetrahydroxanthones). In fact, this outcome points to the biosynthetic origin from anthraquinones by oxidative cleavage to benzophenone intermediates, as already discussed by Holker et al [23] and shown in Scheme 4 with chrysophanol as one possible precursor (20). The oxidative opening of chysophanol leads to type-A xanthones with a C6 methyl group (pathway a; methyl and ester groups on different sides, e.g., 16) or to the respective type-B xanthones with a 3-methyl group (pathway b; methyl and ester groups on the same side, e.g., 17) through the benzophenone intermediates 19 or 21, respectively (Scheme 4).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…In contrast to the globosuxanthones and diversolonic esters (which can be considered to belong to the "type-B" tetrahydroxanthone family), most other hydrogenated xanthones have the ester group at the angular C4a position, as shown in the selected structures 17 and 18 ("type-A" tetrahydroxanthones). In fact, this outcome points to the biosynthetic origin from anthraquinones by oxidative cleavage to benzophenone intermediates, as already discussed by Holker et al [23] and shown in Scheme 4 with chrysophanol as one possible precursor (20). The oxidative opening of chysophanol leads to type-A xanthones with a C6 methyl group (pathway a; methyl and ester groups on different sides, e.g., 16) or to the respective type-B xanthones with a 3-methyl group (pathway b; methyl and ester groups on the same side, e.g., 17) through the benzophenone intermediates 19 or 21, respectively (Scheme 4).…”
Section: Resultsmentioning
confidence: 78%
“…[20,21] Due to their pronounced toxicity, they are classified as mycotoxins. [12,22] The tetrahydroxanthones occur as monomers, for example, as aand b-diversonolic esters, [23,24] monodictysins, [25] or blennolides, the recently isolated monomeric units of secalonic acids.…”
Section: Introductionmentioning
confidence: 99%
“…Modifications of Friedel-Crafts reaction (Scheme 2, a)) have included an acylation in the presence of trifluoroacetic acid anhydride, demethylation, and subsequent cyclization of the benzophenone (with elimination of methanol) in aqueous medium under pressure and heating [43]. Also, a method restricted to 1,3-dihydroxyxanthones included the acylation of an appropriate O,O,O-tris(trimethylsilyl)-substituted phenol with the benzoyl chloride in the presence of stannic chloride [46].…”
Section: Modifications To the Classical Methodsmentioning
confidence: 99%
“…Because intermolecular acylation reactions give generally higher yields than Ullmann ether syntheses, the most prevalent strategy for xanthone synthesis is acylation, followed by cyclization to form the heterocyclic ring [for a practical comparative example see 33]. The xanthone skeleton can also be formed directly from diaryl ester by pyrolysis e) [34,35] or through the above intermediates by photo Fries rearrangement f) [36][37][38][39][40][41][42], or by Smiles rearrangement g) [43,44], strategies that emerged in the last years.…”
Section: Classical Methodsmentioning
confidence: 99%
“…Scheme 4). Elix and co-workers developed this method to synthesize 61 during their study of xanthones from the lichen Rinodina thiomela (Scheme 11) 61. Ester 59 was prepared by condensation of acid 57 and phenol 58 in the presence of N,N´dicyclohexlcarbodiimide (DCC).…”
mentioning
confidence: 99%